Industry-specific knowledge spurs productivity: An application of panel cointegration - Petra Zloczysti (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Using data for 14 OECD countries and 13 sectors for the period 1985-2004, this paper analyzes the significance of the linkage between channels of international knowledge spillovers and total factor productivity. We distinguish between domestic and international intra- and inter-sectoral spillover sources. Patent applications are exploited to estimate the contribution of technology transfer to industrial productivity. To account for technological distance, we weight foreign knowledge by bilateral technological proximity. By adopting estimation methods reflecting recent developments in the treatment of non-stationary panel data econometrics, we find that industry-specific knowledge both nationally and internationally mainly drives productivity in the respective sector.
Keywords: C23; L60; O30; O40; 330; Knowledge Spillover; Total Factor Productivity; Manufacturing; Panel Cointegration; Verarbeitendes Gewerbe; Wissenstransfer; International; Produktivität; Patent; Technologietransfer; Schätzung; OECD-Staaten